Driving high-functioning clinical teams: An advanced practice registered nurse and physician assistant optimization initiative. Issue 6 (June 2020) - Brooks, Paula B.; Fulton, Megan E.
ABSTRACT: Background: Rapid changes in the health care marketplace are driving health care systems to modify operations by which the advanced practice registered nurse (APRN) and physician assistant (PA) clinicians serve patients. By identifying more effective and efficient utilization workflows, organizations can meet these demands resulting in high-functioning clinical teams. Local problem: With the growing number of APRNs and PAs within a large academic medical center, there was a recognized need to establish effective and efficient utilization practices for these health care providers. Methods: Directors of the Advanced Practice Provider Best Practice Center developed an internal nurse practitioner (NP)/certified nurse midwife (CNM)/clinical nurse specialist (CNS)/PA assessment service in which evaluations were conducted to optimize APRN and PA practice at the clinical/department level. This assessment excluded certified registered nurse anesthetists. Interventions: Thirty-two clinical areas were evaluated between September 2016 and May 2019. This included an NP/CNM/CNS/PA survey and over 200 individual NP/CNM/CNS and PA provider interviews. Assessments addressed utilization, billing practices, professional development, and communication among team members. Results: Qualitative and quantitative reports were compiled. Many common themes were identified. These were broken down into three major categories: productivity, clinical operations, and professional development/support. Conclusions: Several recommendations were presented to department leaders regarding NP/CNM/CNS/PA practice. Those departments who implemented several of the recommendations showed positive outcomes. This was evidenced by increased financial gain (increased relative value units, increase in revenue generated), increased patient access (increased clinic densities), and overall NP/CNM/CNS/PA satisfaction.